Corpo desviante: uma poética em performance arte - Costa, Láinon William Ribeiro da (2021)
The research Corpo Desviante consists of the creation of a performative poetics, held in 2019, in the Master’s Degree of the Graduate Program in Visual Arts (PPGART), by the Federal University of Santa Maria (UFSM). The research, inserted in the research line Art and Culture, aimed to carry out the series designed from the performance placing it on the threshold between art and politics. For this, the poetics is anchored in the political and social guidelines LGBTQIA+. The production of poetic restlessness materialized in exercises and artistic experiments that are composed of a deviant body and its memories. The objects, performances and installations were created in order to develop proposals in art that fostered the insurgente political reflection on Queer issues, becoming the center of the object of poetics, bordering the fine boundaries between art and activism. The methodological procedures sought resources and experiences in field research, subsidized by an autoetnographic bias that focuses on the experience in the field with the researcher, his body and other bodies that integrate the poetic constructions connected with contemporary art. Autobiography was also a resource used in creative processes. The authors Goldberg and Taylor affirm and strengthen the performative actions in their practical-theoretical aspects. Regarding the Queer theory, Judith Butler, Paul B. Preciado and Richard Miskolci support the research. In the course, whose record is accompanied by a textual analysis together with the repertoire of images built throughout the elaboration of this series, five works were created. The proposals created are called Gayola, Alvo Fácil, Corpo(ros), CUlhões and Buraco do Sigilo. The contribution of the research work focuses on the discussion of a process of artistic creations in performance that seeks to amalgamate contemporary art centered on political issues of the experiences of the Queer bodies.